Three-dimensional electrospun ECM-based hybrid scaffolds for cardiovascular tissue engineering - Heydarkhan-Hagvall, Sepideh (2008)
Electrospinning using natural proteins or synthetic polymers is a promising technique for the fabrication of fibrous scaffolds for various tissue engineering applications. However, one limitation of scaffolds electrospun from natural proteins is the need to cross-link with glutaraldehyde for stability, which has been postulated to lead to many complications in vivo including graft failure. In this study, we determined the characteristics of hybrid scaffolds composed of natural proteins including collagen and elastin, as well as gelatin, and the synthetic polymer poly(ε-caprolactone) (PCL), so to avoid chemical cross-linking. Fiber size increased proportionally with increasing protein and polymer concentrations, whereas pore size decreased. Electrospun gelatin/PCL scaffolds showed a higher tensile strength when compared to collagen/elastin/PCL constructs. To determine the effects of pore size on cell attachment and migration, both hybrid scaffolds were seeded with adipose-derived stem cells. Scanning electron microscopy and nuclei staining of cell-seeded scaffolds demonstrated complete cell attachment to the surfaces of both hybrid scaffolds, although cell migration into the scaffold was predominantly seen in the gelatin/PCL hybrid. The combination of natural proteins and synthetic polymers to create electrospun fibrous structures resulted in scaffolds with favorable mechanical and biological properties.